Analisis Tingkat Keberhasilan Pemungutan Pajak Daerah Dan Retribusi Daerah Pada Pemerintah Kota Mataram - Indri Mustiani; Lukman Effendy; Nurabiah Nurabiah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the level of success in collecting local taxes and local levies on the local government of Mataram City. The research method used is descriptive quantitative approach with data collection techniques through documentation. The sample is the BKD of Mataram City as the institution in charge of managing the APBD and acting as the Regional General Treasurer (BUD). The results of this study can be concluded that the effectiveness or success rate of tax collection is considered very successful with an average effectiveness for 5 years of 103% so that the Mataram City Regional Finance Agency can be said to be very successful in collecting taxes which are its responsibility with the highest average effectiveness. namely the underground water tax with an effectiveness percentage of 113% because every year there are additional new tax objects along with the increasing number of buildings such as hotels that require groundwater in their management and the lowest average effectiveness is the swiftlet nest tax with a percentage of 7% because it is not a tax potential and tax officials have difficulty in finding entrepreneurs to know the harvest period. While the effectiveness of regional retribution is considered less successful with an average effectiveness for 5 years of 79% so that each SKPD can be said to be less successful in maximizing the potential for retribution it manages with the highest average effectiveness, namely business service retribution with a percentage of 94% and an average effectiveness The lowest average is general service fees with a percentage of 77%. This is because in the retribution grouping there are various types of retribution which are managed by each SKPD so that many factors can affect the achievement of the retribution target. In addition, information regarding the reasons for achieving or not the retribution target is still lacking because the research was only conducted at the Mataram City Regional Finance Agency. The novelty of this research is that researchers analyze the effectiveness of each type of tax and retribution grouping in the city of Mataram. Theoretically, this research can provide broad implications regarding stewardship theory. Practically, this research has implications for the Regional Finance Agency to be better in terms of facilitating the community to pay taxes and being able to monitor each OPD in order to increase their retribution income. Policy-wise, this research has implications for the Regional Finance Agency in order to issue a policy regarding the tax and levy management system that needs to be implemented so that future management can be better and maximal with the condition that the collectors and those who are collected do not feel disadvantaged.